Sur quelques Coleophoridae de la région de Berdjansk (Ukraine). - Baldizzone, Giorgio; Patzak, Helmut (Contributions to Entomology = Beiträge zur Entomologie, 1991)
The work deals with the collection of Coleophoridae (about 250 specimens) collected by Gulinov near Berdjansk (Asov sea) Ucraina, UdSSR. Thirty-nine species have been identified: of them 4 (C. gulinovi, C. ucrainae, C. berdjanski, C. armeniae) new to science, and besides the true female of C. occatella Staudinger has been identified. For several species the knowledge about East European geographic area has been increased. Nomenclatural Acts armeniae Baldizzone & Patzak, 1991 (Coleophora), spec. n. berdjanski Baldizzone & Patzak, 1991 (Coleophora), spec. n. gulinovi Baldizzone & Patzak, 1991 (Coleophora), spec. n. ucrainae Baldizzone & Patzak, 1991 (Coleophora), spec. n.